2017
DOI: 10.1038/s41598-017-07219-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Trigeminal Nerve Stimulation in Severe Traumatic Brain Injury

Abstract: Following traumatic brain injury (TBI), ischemia and hypoxia play a major role in further worsening of the damage, a process referred to as ‘secondary injury’. Protecting neurons from causative factors of secondary injury has been the guiding principle of modern TBI management. Stimulation of trigeminal nerve induces pressor response and improves cerebral blood flow (CBF) by activating the rostral ventrolateral medulla. Moreover, it causes cerebrovasodilation through the trigemino-cerebrovascular system and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 76 publications
3
45
0
Order By: Relevance
“…32,33 In this light, an increasing number of studies have shown that TNS is beneficial for seizure control, depression, and migraine, and, very recently, the FDA approved a clinical trial for TNS treatment of Lennox-Gastaut syndrome. 34 In addition to epilepsy and depression, researchers have proposed a clinical application for VNS and TNS for treating variety of disorders, such as migraine, 35 anxiety, 36 cognitive impairment, 37,38 Alzheimer's disease, 39 autism, 40 tinnitus, 41,42 poststroke symptoms, [43][44][45] post-traumatic stress disorder, 46 eating disorders 47 and obesity. 48 Although clinical trials on the topic are accumulating, most of them are preliminary proof-ofconcept pilot studies obtained with limited sample sizes.…”
Section: Clinical Applications Of Vagus-and Trigeminal-nerve Stimulatmentioning
confidence: 99%
“…32,33 In this light, an increasing number of studies have shown that TNS is beneficial for seizure control, depression, and migraine, and, very recently, the FDA approved a clinical trial for TNS treatment of Lennox-Gastaut syndrome. 34 In addition to epilepsy and depression, researchers have proposed a clinical application for VNS and TNS for treating variety of disorders, such as migraine, 35 anxiety, 36 cognitive impairment, 37,38 Alzheimer's disease, 39 autism, 40 tinnitus, 41,42 poststroke symptoms, [43][44][45] post-traumatic stress disorder, 46 eating disorders 47 and obesity. 48 Although clinical trials on the topic are accumulating, most of them are preliminary proof-ofconcept pilot studies obtained with limited sample sizes.…”
Section: Clinical Applications Of Vagus-and Trigeminal-nerve Stimulatmentioning
confidence: 99%
“…The sympathetic and blood pressure responses to facial cooling are reportedly modified in some disease states (Prodel, Barbosa, Mansur, Nobrega, & Vianna, 2017) and therefore it is quite likely that the cerebrovascular responses are altered too. In rat models of traumatic brain injury, trigeminal nerve stimulation was reported to increase CBF and reduce the development of secondary injury symptoms, such as oedema, blood–brain barrier disruption and lesion volumes (Chiluwal et al., 2017). In humans, therapeutic use of trigeminal nerve stimulation using external electrical stimulation has been examined in neurological, cardiovascular and psychiatric conditions such as epilepsy, depression, attention deficit hyperactivity disorder and post‐traumatic stress disorder (Borsody & Sacristan, 2016; Cook, Abrams, & Leuchter, 2016; Cook, Kealey, & DeGiorgio, 2015; Grahame & Hann, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the trigeminal nerve (CN V) has similar anatomical connections to key brain nuclei as the vagus, including the NTS and locus coeruleus, and has gained an increased research focus as an alternative to VNS as, in humans, it can be more effectively stimulated by superficial, non-invasive, methods. Recently, trigeminal nerve stimulation was also used to reduce cerebral edema, enhance cerebral bloodflow, and improve recovery following severe TBI in rats (56).…”
Section: Discussionmentioning
confidence: 99%